Iron and Vitamin C Supplements for Young Women with Anemia at Islamic Boarding School Addanuriyah Semarang - Witri Hastuti; Amrih Widiati (Humanistic Network for Science and Technology (HNST), 2018)
Young women are at risk of having anemia higher than young men because every month they had menstruation. The purpose of this study was to determine the effectiveness of giving iron and vitamin C supplements to adolescent girls.This is a quantitative research with true experiment design. Research samples were young women who experienced mild-moderate anemia. The study begins with initial screening by measuring Hb levels. The selected samples were given iron supplements in the control group and given iron supplements plus vitamin C in the treatment group. In weeks I and II Fe tablets and vitamin C were given 1 tablet each. Week III, during menstruation the sample is given 1 tablet of Fe and vitamin C every day during menstruation. In week IV given 1 tablet of Fe and vitamin C.The results showed that there were differences in Hb levels in the groups given Fe and Fe tablets plus vitamin C with significance values α = 0.000 and α = 0.000. The average increase Hb in the group with Fe was 1.2 g / dL and in the group given Fe plus vitamin C it was 1.7 g / dL. The group that received Fe and vitamin C tablets was more effective than the group with Fe tablets only. Vitamin C can increase iron absorption when given during menstruation, so it can reduce anemia in young women Keywords: Iron supplements, Vitamin C, Anemia, Young women